2020
DOI: 10.1002/cplu.201900637
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Electrochemiluminescence from Bistridentate Ruthenium(II) Di(quinoline‐8‐yl)pyridine Complexes in Aqueous Media

Abstract: We report the synthesis, photophysics, electrochemistry and electrochemiluminescence (ECL) of two dqp (dqp=2,6‐di(quinoline‐8‐yl)pyridine) based ruthenium(II) complexes, bearing either a n‐butyl ester (1) or the corresponding carboxylic acid functionality (2). The complexes were prepared from [Ru(dqp)(MeCN)3][PF6]2 by reaction with the dqp precursor using microwave irradiation. In both cases, photoluminescence spectra present strong 3MLCT‐based red/near‐infrared (NIR) emissions centred at about 710 nm. The pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…As NIR emissions have a lower background interference, cause less photochemical damage, and have a deeper tissue penetration, NIR-ECL systems have become powerful analytical tools in biomedical and diagnostic fields. The Ru (II) complex [ 61 , 62 ], QDs [ 63 , 64 ], metal NCs [ 41 , 47 , 48 , 49 , 65 , 66 ], nanocrystals [ 46 , 50 ], and perylene diimide [ 67 ] have all been used as NIR-ECL emitters. Tetraphenylenthylene (TPE) NC was synthesised and applied to the aggregation-induced ECL emission method [ 46 ].…”
Section: Current Strategies and Technologies Of The Ecl Systems In Th...mentioning
confidence: 99%
“…As NIR emissions have a lower background interference, cause less photochemical damage, and have a deeper tissue penetration, NIR-ECL systems have become powerful analytical tools in biomedical and diagnostic fields. The Ru (II) complex [ 61 , 62 ], QDs [ 63 , 64 ], metal NCs [ 41 , 47 , 48 , 49 , 65 , 66 ], nanocrystals [ 46 , 50 ], and perylene diimide [ 67 ] have all been used as NIR-ECL emitters. Tetraphenylenthylene (TPE) NC was synthesised and applied to the aggregation-induced ECL emission method [ 46 ].…”
Section: Current Strategies and Technologies Of The Ecl Systems In Th...mentioning
confidence: 99%
“…[4][5][6][7] In that context, ruthenium and iridium complexes remain attractive despite their extremely low luminescence efficiencies and short excited state lifetimes in near-infrared region. [8][9][10][11] On the other hand, organic dyes offer a wide chemical diversity with highly tunable photophysical and electrochemical characteristics. [12][13][14][15] The electronic characterization of a new family of dyes featuring a helical geometry was reported recently.…”
Section: Near-infrared Electrochemiluminescence In Water Through Regimentioning
confidence: 99%
“…[13][14][15]21 However, a major challenge is to obtain such bright organic ECL emitters operating in physiological conditions (i.e. in aqueous buffer at pH 7.4 where bioassays and cell microscopy are relevant), especially in the near-infrared region 11,22 due in part to strong nonradiative processes as governed by the energy gap law. 23 Indeed, this spectral domain is particularly attractive for Scheme 1 Structure and preparation of water-soluble helicene derivatives.…”
Section: Near-infrared Electrochemiluminescence In Water Through Regimentioning
confidence: 99%
“…[27] Recent studies towards finding more promising ruthenium metalloligands have shown that the derivatives of the metal complexes of Ru(dqp) 2 2 + (dqp: 2,6-di(quinolin-8-yl)-pyridine) hold promising properties. [28][29][30][31] The Ru(dqp) 2 2 + complexes have an excited-state lifetime in the μs time-scale, as well as comparable extinction coefficients and absorption profile in the visible region to Ru(bpy) 3 2 + and Ru(tpy) 2 2 + complexes. The dqp ligand also provides a larger bite angle than the Ru(tpy) 2 2 + complexes, resulting in an increase in the ligand field splitting.…”
Section: Introductionmentioning
confidence: 99%
“…The Ru(tpy) 2 2+ complexes, despite providing a more ideal trans configuration, has much less useful excited‐state lifetime of just 250 ps [27] . Recent studies towards finding more promising ruthenium metalloligands have shown that the derivatives of the metal complexes of Ru(dqp) 2 2+ (dqp: 2,6‐di(quinolin‐8‐yl)‐pyridine) hold promising properties [28–31] . The Ru(dqp) 2 2+ complexes have an excited‐state lifetime in the μs time‐scale, as well as comparable extinction coefficients and absorption profile in the visible region to Ru(bpy) 3 2+ and Ru(tpy) 2 2+ complexes.…”
Section: Introductionmentioning
confidence: 99%